Bachelard et le matérialisme : conséquences ontologiques sur le matérialisme, l’énergie et les éléments - Kafure, Gabriel (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2021)
This work seeks in understanding in what consists the epistemological rupture and the poetic distortion of the concept of materialism in Bachelard. Due to the existence of two epistemological vectors resulting from the dialectical complementarity between applied rationalism and technical rationalism there is no metaphysical fixity. In this sense, this fundamental aspect of this metaphysics for science and rational perspective of Bachelard leads to the criticism of the relationship between matter and form so that it is possible to question the tendency of an understanding of matter as always metaphysically subject to form. Beyond the matter depends on the point of view and the knowledge of each. Thus, the knowledge of Bachelard required a dis-subjectivation and a dis-objectivation of his materiality with a view to a new development of the relationship between matter and energy. Bachelor’s concepts can thus enrich the questioning of a philosophical matter and a scientific materialism which achieves a break between realism and empiricism. In Rational Materialism, Bachelard will approach the starting point of matter through three types of materialism. Rational Materialism can probably be considered the author’s last epistemological work. This paper therefore claims to lead us to a vision of trans-subjectivity and of the deconstruction of the objectivity of bachelardian materialism. Keywords: Matter, Alchemy, Energy, Metaphysics, Contemporary Physics.